Mammalian‐enabled (MENA) protein enhances oncogenic potential and cancer stem cell‐like phenotype in hepatocellular carcinoma cells. Issue 8 (22nd June 2017) - Hu, Kunpeng; Huang, Pinzhu; Luo, Hui; Yao, Zhicheng; Wang, Qingliang; Xiong, Zhiyong; Lin, Jizong; Huang, He; Xu, Shilei; Zhang, Peng; Liu, Bo
Abstract : Mammalian‐enabled (MENA) protein is an actin‐regulatory protein that influences cell motility and adhesion. It is known to play a role in tumorigenicity of hepatocellular carcinoma (HCC) but the underlying molecular mechanism remains unknown. This study aimed to investigate the oncogenic potential of MENA and its capacity to regulate cancer stem cell (CSC)‐like phenotypes in HCC cells. Real‐time‐PCR and western blot were used to assess mRNA and protein levels of target genes in human HCC tissue specimens and HCC cell lines, respectively. Stable MENA‐overexpressing HCC cells were generated from HCC cell lines. Transwell cell migration and colony formation assays were employed to evaluate tumorigenicity. Ectopic expression of MENA significantly enhanced cell migration and colony‐forming ability in HCC cells. Overexpression of MENA upregulated several hepatic progenitor/stem cell markers in HCC cells. A high MENA protein level was associated with high mRNA levels of MENA, CD133, cytokeratin 19 (CK19), and epithelial cell adhesion molecule (EpCAM) in human HCC tissues. Overexpression of MENA enhanced epithelial‐to‐mesenchymal transition (EMT) markers, extracellular signal‐regulated kinases (ERK) phosphorylation, and the level of β‐catenin in HCC cells. This study demonstrated that overexpression of MENA in HCC cells promoted stem cell markers, EMT markers, and tumorigenicity. These effects may involve, at least partially, the ERK and β‐catenin signaling pathways. Abstract : We investigated the oncogenic potential of mammalian‐enabled (MENA) protein and its capacity to regulate cancer stem cell (CSC)‐like phenotypes in hepatocellular carcinoma (HCC). Overexpression of MENA significantly enhanced migration and colony‐forming abilities, upregulated several hepatic progenitor/stem cell markers, as well as enhanced epithelial‐to‐mesenchymal transition (EMT) markers in HCC cells.